Framework Management to Minimize Risk in Protecting Enterprise Systems: Systematic Literature Review - Soni Adiyono; Romy Aziz Risaldi; Aris Puji Widodo; Eko Sediyono (Telematika, 2022)
Purpose: This study aims to determine the efforts to minimize the occurrence of risks in enterprise systems and how far the framework is applied to an organization, as well as what steps must be applied in anticipation of it.Design/methodology/approach: This study uses a systematic review research method of literature published by international journals in the period 2016 to 2021 which is subscribed to by Diponegoro University.Findings/result: Most of the selected journals stated that in an effort to secure enterprise systems in an organization, they really consider several aspects in it, especially in terms of cost which is one of the biggest considerations in it, besides that support from policy makers must be needed to make guidelines in implementing framework (framework) regarding the limitations of Authentication access and interaction on a system.Originality/value/state of the art: the method applied will focus on discussing the realm of enterprise systems, specifically discussing framework management in an effort to minimize risks to enterprise systems.